Diachronic analysis of medieval livestock and present-day bullfighting livestock: effects on territorial structure in Cádiz province (Spain) - Fernández-Enríquez, Alfredo; Ruiz-Pilares, Enrique José; Ramírez-Guerrero, Gema (Revista de Estudios Andaluces, 2023)
Livestock´s relevance in the productive structuring of the Cadiz territory has been documented since the late Middle Ages, when the leasing of pastures outlined a dividing line between agricultural and livestock uses, located respectively north and south of the Guadalete River and its main tributary, the Majaceite river. Subsequent agricultural expansion pointing south has substantially masked the geographical factors causing this clear distribution. Its analysis allows for the detection of locational patterns similar to the current bullfighting livestock enclosures. In conclusion, the coevolution of livestock and landscape in southern Cadiz countryside has created an exceptional natural and historical-cultural heritage, hallmarks to be preserved as a fundamental asset in the necessary territorial reactivation.